Advances in CMV Management: A Single Center Real-Life Experience - Malagola, Michele; Pollara, Caterina; Polverelli, Nicola; Zollner, Tatiana; Bettoni, Daria; Gandolfi, Lisa; Gramegna, Doriana; Morello, Enrico; Turra, Alessandro; Corbellini, Silvia; Signorini, Liana; Moioli, Giovanni; et al. (Frontiers in Cell and Developmental Biology, 2020)
CMV infection is a major challenge in allogeneic stem cell transplantation (allo-SCT). The changing landscape in CMV management regards the introduction of letermovir in prophylaxis of high-risk patients and the source of CMV DNA monitoring (plasma – PL vs whole blood – WB), for pre-emptive therapy (PET) initiation. We report here how our real-life experience in CMV management evolved, following letermovir registration. We focus on the effects of a systematic use of letermovir for CMV prophylaxis in high-risk patients and the results of a longitudinal comparison of CMV DNAemia monitoring in PL and WB. From December 2018 to April 2020, 60 allo-SCTs have been performed in our Center (LET ERA). Letermovir was used in prophylaxis from day 0 to day +100 in 45 cases, alli CMV IgG positive. 7/45 patients (15%) developed a clinically significant CMV infection The incidence of CMV clinically significant infection by day +100 in the LET ERA was 8% (5/60 cases) and this favorably compares with the 44% observed in a cohort of 41 allo-SCT performed between November 2017 and November 2018 (NO LET ERA) (p=0,0006) Similarly, the incidence of CMV disease significantly reduced from 12% in the NO LET ERA to 2% in the LET ERA (p=0,02). Overall the prophylaxis was well tolerated and no side effects were reported. Furthermore, from February to May 2019, we comparatively measured CMV DNA from WB and PL and we confirmed that there was a linear correlation between CMV DNA level in WB and PL (Spearman’s test r=0.86). Moreover, CMV DNAemia at the time of PET in the 12 patients with clinically significant CMV infection was non significantly higher in WB versus PL (5.202 vs 4.981 copies/ml, p=0.1). Our real-life experience confirms that: i) letermovir is highly effective and safe, leading to a significant drop in CMV clinically significant infections; ii) WB may be an effective alternative to PL as a source for CMV DNA monitoring, as a linear correlation of DNAemia was confirmed between WB and PL, even if the CMV DNAemia at PET initiation was comparable in the two sources.